Zande harp music - Giorgetti, Filiberto (International Library of African Music, 1965)
The physical part of this study is very interesting, on the way in which the instrument kundi can be made. I did not have either the patience or the time to dedicate myself to such study. I first met this instrument in November 1926. I was interested in the nostalgic sound and the pathetic tune of Kundi, besides its gay sounds, more than I was interested in its making.
Keywords: Ethnomusicology; Harp; Music; Musical instruments; Zande (African people); Africa; Central Africa; African Music